Analysis of a pharmaceutical batch freeze dryer: resource consumption, hotspots, and factors for potential improvement. Issue 12 (10th September 2019) - Renteria Gamiz, Ana Gabriela; Van Bockstal, Pieter-Jan; De Meester, Steven; De Beer, Thomas; Corver, Jos; Dewulf, Jo
Abstract: Whilst freeze drying is known for its high energy requirements, few studies have been conducted assessing the efficiency of freeze dryers, especially related to pharmaceuticals. A quantitative analysis is conducted on a batch freeze dryer used for biopharmaceuticals, aiming to calculate the process efficiency and to identify the components causing the highest resource consumption as well as factors for potential improvement. Exergy and energy analysis were performed combining experimental and modeled data. The process showed a task efficiency (exergy efficiency) lower than 1%. This value is influenced by the low Coefficient of Performance of the refrigeration cycle as well as the large mass of steel in the device which is heated up and cooled down throughout the process.